1998
DOI: 10.1073/pnas.95.25.15072
|View full text |Cite
|
Sign up to set email alerts
|

Early physiological abnormalities after simian immunodeficiency virus infection

Abstract: Central nervous system (CNS) damage and dysfunction are devastating consequences of HIV infection. Although the CNS is one of the initial targets for HIV infection, little is known about early viral-induced abnormalities that can affect CNS function. Here we report the detection of early physiological abnormalities in simian immunodeficiency virus-infected monkeys. The acute infection caused a disruption of the circadian rhythm manifested by rises in body temperature, observed in all five individuals between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
39
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 42 publications
6
39
0
Order By: Relevance
“…Subcutaneous body temperature data are not identical to 'core' body temperature but are likely closely correlated in the macaque. For this study, mean temperature before challenge was about 11C lower than values reported for intraperitoneal temperature in Japanese (Takasu et al, 2002) and pigtail (MR Weed, personal communication) macaques; this was consistent with prior reports for subcutaneous temperature in cynomolgous (Almirall et al, 2001) and rhesus (Horn et al, 1998) macaques. The circadian patterns of temperature regulation appear highly similar between s.c. and i.p.…”
Section: Discussionsupporting
confidence: 91%
“…Subcutaneous body temperature data are not identical to 'core' body temperature but are likely closely correlated in the macaque. For this study, mean temperature before challenge was about 11C lower than values reported for intraperitoneal temperature in Japanese (Takasu et al, 2002) and pigtail (MR Weed, personal communication) macaques; this was consistent with prior reports for subcutaneous temperature in cynomolgous (Almirall et al, 2001) and rhesus (Horn et al, 1998) macaques. The circadian patterns of temperature regulation appear highly similar between s.c. and i.p.…”
Section: Discussionsupporting
confidence: 91%
“…SIV inoculation was performed via the saphenous vein using a cell-free viral stock (SIVmac182) obtained after serial passage of SIVinfected microglia (10). Animals received 1 mL of SIVmac182 in RPMI-1640, containing 0.5 ng/mL p27 (gag) antigen; this dose is equivalent to 10 3 tissue culture infectious doses when titered on CEMx174 cells.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous movement and temperature analysis was performed using radiotelemetry with implantable transmitters, cage-mounted receivers, and software data acquisition program purchased from Data Sciences (St. Paul, Minnesota, USA) as described previously (10). To account for individual differences in gross motor activity, data from individual monkeys were normalized against the average of a 14-day baseline period (preinoculation for SIV groups, preceding saline injection for the PMPA-only group).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CNS infection occurs during primary SIV infection (7), and the degree of CNS pathology varies among animals (6,17,26,39,48). For chronically infected macaques, a significant decrease in viral RNA is observed in the CNS, even though viral DNA persists (8).…”
mentioning
confidence: 99%